Analisis Kecerdasan Ekologis Berbasis Kearifan Lokal pada Siswa SMA Di Desa Jaring Halus Kecamatan Sicanggang dalam Pemanfaatan dan Pelestarian Hutan Mangrove - Nasution, Dwi Qorianti; Syarifuddin, Syarifuddin; Manurung, Binari (Jurnal Pendidikan Biologi, 2016)
This study aims to : (1) Determine the Level of Intelligence Ecological high school students based Local Wisdom in Utilizing And Preserving Forests Mangrove in the village of Jaring Halus of Sicanggang District Langkat;(2) Knowing Bioethics taught by Biology Teacher on high school students in Utilizing And Preserving mangrove forest in the village of Fine Jaring District of Sicanggang Langkat;(3) Knowing the Family Education taught parents to their children who are in the Village District of Jaring Fine Sicanggang Langka;(4) Knowing how students learn in Utilizing Local Wisdom and Preserving mangrove forest in the village of Fine Jaring District of Sicanggang Langkat . The approach used is a descriptive study non hypotheses using survey approach ( surveying Method). The research sample of 30 high school students who reside in the village of Jaring Fine Sicanggang District of Langkat . instrument used in this study is a test, questionnaire , interview and observation . Data analysis technique used is descriptive analysis with percentages . The final conclusion;(1) Ecological Intelligence Level High School Students Based Local Wisdom on average relatively good with an average score of ecological intelligence level of 22.5 % of high school students;(2) the ability of high school students Against Ecological Intelligence Bioethics Teachers Taught average quite well with the mean the ability of high school students average score of 50.7 %;(3) Family Education Level Taught His parents People Against the average is quite good with an average score of level of education was 35.8 % ;(4) knowledge in ecological intelligence level of high school students based on local wisdom on average relatively good with an average score of knowledge amounting to 25.56 % of high school students.